PERFORMANCE EVALUATION OF Fe (III) ADSORPTION ONTO BREWERS’ SPENT GRAIN (Nigerian Journal of Technology, 2016)
This work investigated the performance of locally available brewer’s spent grain (BSG) as an adsorbent for the removal of Fe (III) from aqueous solution. The brewer’s spent grain (BSG) was collected, processed and characterized using scanning electron microscope (SEM) and X-ray fluorescence (XRF) to assess its potential for the removal of Fe (III). Thereafter, batch adsorption technique was employed to evaluate the effects of adsorption variables such as pH, initial metal ion concentration, adsorbent dosage and contact time on the sorption efficiency of BSG. The maximum adsorption time was fixed at 120minutes with a stirring speed of 100rpm. Experimental data obtained were then analyzed using selected isotherms and kinetic models such as Langmuir isotherm, Freundlich isotherm, Pseudo-First order and Pseudo-Second order kinetic models. SEM result revealed the presence of microporous structure within the surface of BSG thus making it a good candidate for metal ion removal. Based on the linear coefficient of determination (r2), it was observed that the experimental data fitted well with the Langmuir isotherm model (r2 = 0.9940 for raw BSG and 0.9946 for the treated BSG). In addition, the reaction mechanism that accompanies the adsorption of Fe (III) unto BSG was best described by the pseudo-second order kinetic model (r2 = 0.9823 for raw BSG and 0.981 for the treated BSG). Finally, maximum adsorption efficiencies of 66% and 77% were obtained for both the raw and treated BSG for optimum adsorption time of 120 minutes, pH 8.0 and adsorbent dose of 1.0g/50ml solution. http://dx.doi.org/10.4314/njt.v35i4.36